Effects of deficit irrigation on two cherry tomato cultivars in hilly areas - Pulvento C.; Riccardi M.; D'Andria R.; Lavini A.; Calandrelli D. (Irrigation in Mediterranean agriculture: challenges and innovation for the next decades, 2008)
In the last years the cultivation of cherry tomato significantly increased in the hilly areas of Campania region. Generally in the Campania hilly areas the species are cultivated under rainfed conditions to improve some quality parameters. The cultivation without irrigation is feasible thanks to the resistance to abiotic stress of cherry tomato and because climatic conditions of hilly areas of the region are characterized by erratic rainfall during the summer. The aim of the present work was to evaluate the response to deficit irrigation scheduling based on critical plant growth stages to ensure good productivity of two cultivars of cherry tomato (Altavilla cv. standard and Mignon hybrid). The trial was carried out in 2005 and 2006 at the experimental station of the CNR-ISAFoM, in Piano Cappelle (BN). The two cultivars were subjected to four irrigation regimes: T0 (rainfed), T1 (one irrigation at beginning of flowering), T2 (one irrigation at beginning of flowering and another at 50 percent of fruit set) and T3 (at beginning of flowering, at 50 percent of fruit setting and, after, every 15 days). Results showed that, in the area of the experiment, a limited water supply is useful to increase yield depending on the climate of the year and that it is possible to obtain high quality cherry tomatoes yield also with a limited irrigation water supply.
International Conference on Irrigation in Mediterranean Agriculture: Challenges and Innovation for the Next Decades, 2008/06/17-18, Naples (Italy)